Faktor-Faktor Yang Mempengaruhi Ketepatan Waktu Pelaporan Keuangan - M Sandy Kurniawan; Haninun Haninun (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2023)
Timeliness is an important characteristic in the financial statements of companies going public, the faster the time for submission of financial reports the more relevant the quality of the information. In order for companies to report their financial reports to the public in a timely manner, they must pay attention to the factors that affect the timeliness of financial reporting. The purpose of this study is to analyze the effect of profitability, leverage, liquidity, KAP reputation and company size on the timeliness of financial reporting. The object of research is a manufacturing company listed on the Indonesia Stock Exchange for the 2019-2021 period. The sample selection technique used a purposive sampling technique which resulted in 73 companies based on 4 predetermined criteria. Using the logistic regression analysis method using SPSS software version 18. The results showed that leverage and firm size had a positive effect on the timeliness of financial reporting, while profitability, liquidity and KAP reputation had no effect on the timeliness of financial reporting